2012
DOI: 10.15809/irriga.2012v17n4p408
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de irrigação para otimização do rendimento e qualidade de frutos de tomateiro em sistema de plantio direto

Abstract: Palavras-chave: Lycopersicum esculentum Mill., potencial de água no solo, ºBrix, pH. MOREIRA, J. A. A.; CARDOSO, A. F.; COSTA, L L.; RODRIGUES. M. R.; PEIXOTO, N.; BRAZ, L. T. IRRIGATION MANAGEMENT TO OPTIMIZE THE YIELD AND FRUIT QUALITY OF TOMATO CROP IN NO TILLAGE SYSTEM ABSTRACTThere is much information on the adequate soil water matrix potential for returning irrigation in conventional soil tillage systems; however there is not enough information on the best soil water matrix potential for no-tillage produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
2
5
0
4
Order By: Relevance
“…The results of yield corroborate those found by Koetz et al (2008), Moreira et al (2012) and Silva et al (2018), in Cerrado area of Jataí, Ipameri and Morrinhos in Goiás, with the hybrid 'Heinz 9498' , cultivar 'Hypeel' and hybrid 'BRS Sena' , respectively. These authors concluded that, under water deficit, tomato yield is compromised.…”
Section: Tfy Wp V =supporting
confidence: 86%
See 1 more Smart Citation
“…The results of yield corroborate those found by Koetz et al (2008), Moreira et al (2012) and Silva et al (2018), in Cerrado area of Jataí, Ipameri and Morrinhos in Goiás, with the hybrid 'Heinz 9498' , cultivar 'Hypeel' and hybrid 'BRS Sena' , respectively. These authors concluded that, under water deficit, tomato yield is compromised.…”
Section: Tfy Wp V =supporting
confidence: 86%
“…Water replacement in the soil by irrigation, in appropriate amount and time, is decisive for success of tomato crop because water is one of the factors that most limit the development, yield and industrial quality of tomato fruits (Koetz et al, 2010;Moreira et al, 2012;Nangare et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, irrigation should be adequately managed respecting the water requirement of the crop during its cycle, and the estimation of evapotranspiration is important in this determination (Xie & Zhu, 2013). Recent studies have been carried out to evaluate the effects of drip irrigation depth on productivity and/or quality of tomato fruits, be it for industrial processing (Moreira et al, 2012;Silva et al, 2013) or for in natura consumption (Campagnol, Abrahão, Mello, Oviedo, & Minami, 2014;Brito et al, 2015). However, studies correlating irrigation depth with the production and quality of cherry tomatoes are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Os indicadores para determinar o momento de irrigar e a quantidade de água a ser aplicada nas culturas, podem ser agrupados em indicadores de manejo com base na planta, no solo e no clima (FRIZZONE et al, 2012;SEDIYAMA;VILLA NOVA, 2013). O manejo da irrigação no tomateiro industrial depende da textura do solo, sua capacidade de retenção de água, cultivar, condições climáticas e do sistema de irrigação SILVA, 2007;MOREIRA et al 2012).…”
Section: Manejo Da Irrigação Em Tomate Para Processamentounclassified
“…O estádio de frutificação do tomateiro é o mais sensível à deficiência hídrica no solo, em que irrigações inadequadas comprometem o rendimento e a qualidade de fruto (PRIETO, 1997;KOETZ et al, 2010;BECKLES, 2012). Para melhorar a qualidade dos frutos é conveniente reduzir o intervalo das irrigações, diminuir a quantidade de água na fase de maturação dos frutos e antecipar a última irrigação antes da colheita (KOETZ et al, 2010;LOPES, 2010;MOREIRA et al 2012), embora tais práticas têm ocasionado menor produtividade em função do deficit hídrico na cultura (PATANÈ; COSENTINO, 2010; PATANÈ; TRINGALI; SORTINO, 2011).…”
Section: Introductionunclassified